388 Short-course HIPEC at the time of interval debulking surgery for high tumor burden ovarian cancer: preliminary results of a pioneering clinical trial in brazil. (18th September 2019) - Batista, T; Carneiro, V; Tancredi, R; Badiglian-Filho, L; Sarmento, B; Costa, R; Lopes, A; Vieira, M; Lissa, F; Leão, C
Abstract : Objectives: To present the postoperative outcomes in our ongoing clinical trial. Methods: Cross-sectional analysis of early data from our phase 2 trial – an open-label, multicenter, single-arm trial on the safety and efficacy of neoadjuvant chemotherapy (NACT) followed by fast-track cytoreductive surgery (CRS) plus short-course HIPEC in advanced ovarian cancer (ClinicalTrials.gov: NCT02249013 ). Results: Fifteen patients with stage IIIB (n=1) or IIIC (n=14) epithelial malignancies were enrolled until July, 2019. The median (range) age was 46 years (19–67), with preoperative serum CA125 levels of 737.7U/mL (161.6–6550). The median number of NACT cycles was 3 (2–4), resulting in PCI scores of 11 (3–18) at the time of CRS/HIPEC – developed after 29 days (26–43) from the last NACT cycle. Time to restarts i.v. chemotherapy was 39 days (31–74). Median operation time was 490 minutes (235–865), with 9 patients requiring major bowel resection as rectosigmoidectomy (n=8) or partial colectomy (n=1). Median length of hospital stay was 5 days (3–10), with ICU stay of 1 day (1–5). Four patients experienced no postoperative complications, whereas 5 suffered only minor G1/G2 complications, and 6 suffered major G3 complications, according to the NCI/CTCAE classification. The most common complications were electrolytes imbalance and anemia. Two patients experienced reoperation because of G3 postoperative hemorrhage or peritoneal infection, whereas no deaths were recorded. Conclusions: Our protocol seems to be feasible and safe, with manageable low rates of short- and middle-term complications. Recruitment to this pioneering clinical trial in Brazil is ongoing.